2016
DOI: 10.1136/bmjopen-2015-009023
|View full text |Cite
|
Sign up to set email alerts
|

New South Wales Child Development Study (NSW-CDS): an Australian multiagency, multigenerational, longitudinal record linkage study

Abstract: PurposeThe initial aim of this multiagency, multigenerational record linkage study is to identify childhood profiles of developmental vulnerability and resilience, and to identify the determinants of these profiles. The eventual aim is to identify risk and protective factors for later childhood-onset and adolescent-onset mental health problems, and other adverse social outcomes, using subsequent waves of record linkage. The research will assist in informing the development of public policy and intervention gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 8 publications
0
73
0
Order By: Relevance
“…Data were drawn from a multiagency administrative record linkage study combined with cross‐sectional survey data for a cohort of 87,026 children and their parents (Carr et al., ). Probabilistic record linkage was conducted by the NSW Centre for Health Record Linkage (CHeReL; http://www.cherel.org.au/) according to nationally legislated privacy protocols, combining routinely collected administrative records related to each child's birth, health, education, and welfare status, as well as parental (health) records for 72,245 children (83% of the cohort) whose births were registered in the state of New South Wales (NSW), Australia (Carr et al., ); the false positive linkage rate was ≤0.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Data were drawn from a multiagency administrative record linkage study combined with cross‐sectional survey data for a cohort of 87,026 children and their parents (Carr et al., ). Probabilistic record linkage was conducted by the NSW Centre for Health Record Linkage (CHeReL; http://www.cherel.org.au/) according to nationally legislated privacy protocols, combining routinely collected administrative records related to each child's birth, health, education, and welfare status, as well as parental (health) records for 72,245 children (83% of the cohort) whose births were registered in the state of New South Wales (NSW), Australia (Carr et al., ); the false positive linkage rate was ≤0.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Data were drawn from the New South Wales Child Development Study (NSW-CDS; ; Carr et al 2016), which uses multi-agency data linkage to combine population records for a cohort of 87 026 children and their parents. Linkage of data from early childhood (birth to 5 years) was completed in 2014 by an independent agency, the Centre for Health Record Linkage (), using probabilistic linkage methods and with adherence to strict privacy protocols (researchers received de-identified records only).…”
Section: Methodsmentioning
confidence: 99%
“…Linkage of data from early childhood (birth to 5 years) was completed in 2014 by an independent agency, the Centre for Health Record Linkage (), using probabilistic linkage methods and with adherence to strict privacy protocols (researchers received de-identified records only). Matching variables included name, date of birth, residential address and sex (for detail on linkage methods and data collections, see Carr et al 2016). Ethical review was conducted by the NSW Population and Health Services Research Ethics Committee (HREC/11/CIPHS/14), with data custodian approvals granted by the relevant government departments.…”
Section: Methodsmentioning
confidence: 99%
“…This research was conducted as part of the New South Wales Child Development Study (NSW-CDS) in Australia (Carr et al, 2016;Green et al, in press). The NSW-CDS is a multi-agency, intergenerational data linkage study that brings together diverse health, education, welfare, and justice records in a population cohort of approximately 90,000 children and their parents.…”
Section: Research Contextmentioning
confidence: 99%
“…It offers the opportunity to address the question: Does whole-school mental health promotion make a difference to the social, emotional, behavioural and educational outcomes of children? Such work is envisaged to occur within the NSW-CDS cohort (Carr et al, 2016; in press), via linkage to the self-reported Middle Childhood Survey mental health and wellbeing outcomes gathered from children at approximately 11 years of age, in their final year of primary schooling (Laurens et al, 2017), as well as multi-agency administrative records (Carr et al, 2016;Green et al, in press). Accordingly, examining the relationship between the SSPESH and student social emotional health over time is beyond the scope of the present paper, but will be explored in subsequent manuscripts from the study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%